Evaluasi Kampung Kota Berkelanjutan Melalui Pendekatan Asian New Urbanism (Studi Kasus: Kampung Jambangan Kota Surabaya) - Siti Nuurlaily Rukmana; Sucipto Sucipto (Jurnal Planologi, 2020)
The success of the Jambangan Village as one of the best environmental management icons in Surabaya city and as a village that has won an award as the Best of the Best Category in 2011 became a unique phenomenon to be studied. To evaluate the preservation of the Jambangan Village, this study used the Asian New Urbanism Approach. This approach was chosen because it is seen from the suitability of the life behavior of East Asian people who have a yard in each of their houses even with minimal land conditions. There were two aspects examined in this study, including evaluating the existence of Jambangan Village with the Asian New Urbanism approach and followed by analyzing the model of sustainable villages. The method used was descriptive qualitative and evaluative with percentage analysis and triangulation analysis techniques. The results obtained showed that Jambangan Village has implemented a model of sustainable village with the Asian New Urbanism approach of 80%, while the model of sustainable village of Jambangan Village is called the “Kampong Improvement Model”, which has 5 important points, consisting of the provision of space for economic activities, suitability of spatial use and policies, capital spread towards the society, cooperation for the improvement of the quality of the village, and socialization for the improvement of the quality of human resources Keywords: Asian New Urbanism, Sustainable Village, Triangulation